2021
DOI: 10.3389/fphar.2021.791644
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosomal miRNAs as Novel Biomarkers Perform Superior Diagnostic Efficiency Compared With Plasma miRNAs for Large-Artery Atherosclerosis Stroke

Abstract: Recently, exosomal miRNAs have been reported to be associated with some diseases, and these miRNAs can be used for diagnosis and treatment. However, diagnostic biomarkers of exosomal miRNAs for ischemic stroke have rarely been studied. In the present study, we aimed to identify exosomal miRNAs that are associated with large-artery atherosclerosis (LAA) stroke, the most common subtype of ischemic stroke; to further verify their diagnostic efficiency; and to obtain promising biomarkers. High-throughput sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
1
9
0
3
Order By: Relevance
“…Exosomes derived from neural stem cells are involved in neuroinflammation, apoptosis, and inhibition of neural regeneration via an miR-219a-2-3p-dependent mechanism (Ma et al, 2019), and overexpression of miR-219a-2-3p could promote apoptosis by suppressing MDM2 expression . miR-379-5p is related to fatty acid metabolism and metabolic pathways, and plays an important role in the pathophysiology of atherosclerosis and stroke (Niu et al, 2021). However, neuron-astrocyte coupling of fatty acid metabolism is essential for neuron survival (Ioannou et al, 2019;Qi et al, 2021), and fatty acid metabolism of neurons is also of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes derived from neural stem cells are involved in neuroinflammation, apoptosis, and inhibition of neural regeneration via an miR-219a-2-3p-dependent mechanism (Ma et al, 2019), and overexpression of miR-219a-2-3p could promote apoptosis by suppressing MDM2 expression . miR-379-5p is related to fatty acid metabolism and metabolic pathways, and plays an important role in the pathophysiology of atherosclerosis and stroke (Niu et al, 2021). However, neuron-astrocyte coupling of fatty acid metabolism is essential for neuron survival (Ioannou et al, 2019;Qi et al, 2021), and fatty acid metabolism of neurons is also of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…These and other results suggest hsa-miR-204 probably acts as a key molecule in the development of AS in RA and deserves further study. In addition, hsa-miR-377, hsa-miR-493, and hsa-miR-525-5p have been reported in either RA or AS (68)(69)(70)(71)(72)(73), and whether these miRNAs take part in the other disease is also worthy of further investigation.…”
Section: Ctssmentioning
confidence: 97%
“…miR‐1296‐5p is associated with cell adhesion molecules and plays a key role in atherosclerosis. miR‐369‐3p, miR‐493‐3p, miR‐379‐5p, and miR‐1296‐5p are promising biomarkers for the diagnosis of LAA stroke 269 . Another study reported that lnc_000048, lnc_001350, and lnc_016442 in exosomes could effectively diagnose LAA stroke.…”
Section: Exosomes In Neuropsychiatric Disordersmentioning
confidence: 99%
“…miR‐369‐3p, miR‐493‐3p, miR‐379‐5p, and miR‐1296‐5p are promising biomarkers for the diagnosis of LAA stroke. 269 Another study reported that lnc_000048, lnc_001350, and lnc_016442 in exosomes could effectively diagnose LAA stroke. lnc_001350 and lnc_016442 significantly improved the prediction of NIHSS in the prognosis of LAA stroke.…”
Section: Exosomes In Neuropsychiatric Disordersmentioning
confidence: 99%